Strategi Bisnis Internet Zappos.Com - Kurniali, Sartika (Bina Nusantara University, 2013)
Zappos established in 1999 runs its business by selling shoes online (e-commerce). The founder of the company originally wanted to provide the most diverse selection to its customers by providing all the brands, styles, sizes, and colors. Now Zappos begins to expand its product line. Zappos organizes all aspects of its business (including the hiring, organization's culture, call center, inventory, website, and supply chain) to provide the best service that gives a